Quality of Scientific Activity, Technology Transfer and Research Integrity: Case of Ukrainian University - Artyukhov, Artem; Krmela, Jan; Krmelová, Vladimíra; Volk, Iurii (My University, 2021)
The article analyzes the relationship between the concepts “quality of scientific activity”, “technology transfer” and “research integrity”. The main task of research is to offer practical tools for maintaining research integrity as elements of the internal and external quality assurance system of education and research. One of the working hypotheses of the study is the correlation between the quality of educational activities at the university, the quality of research and the level of interest of customers of innovative developments in the process of transfer and commercialization of research results. The first two components are determined by the “purity” of research through the implementation of the principles of research integrity. The schematic relationship between the individual goals of sustainable development characterizes the relationship “university − the quality of research − technology transfer – industry”. A logical scheme between research integrity, technology transfer and procedures for internal and external research quality assurance is proposed. The abstract-logical method and the method of induction-deduction were used to analyze the relationship between the concepts of “quality of scientific activity”, “technology transfer” and “research integrity”. Bibliometric analysis was performed using SciVal and VOSviewer tools based on data from the scientific-metric databases Scopus and Web of Science. Based on the bibliometric analysis, it was found that the query “research integrity” identifies the main violations of research integrity and shows a strong link between the quality of research and success in the transfer of knowledge and technology from university to industry. The main problems of the development of technology transfer between the university and industry at the national level are analyzed. A separate block of problems related to research integrity is identified. The case of the national university on creation of university system of maintenance of research integrity and development of infrastructure of maintenance of scientific activity within the limits of the specified system is resulted. The results of the work can be useful for the triangle “business education-science” to reconcile the interests of all the “vertices” of the triangle under the mandatory condition – ensuring the quality of educational and research activities in universities as centers of intellectual potential.
Kvalita vědecké činnosti, transfer technologií a integrita výzkumu: Případ ukrajinské univerzity
Keywords: technology transfer; sustainable development; research integrity; research quality; business university model; transfer technologií; udržitelný rozvoj; integrita výzkumu; kvalita výzkumu; model obchodní univerzity